The Determinants of Bank Default Risk: Evidence from Commercial Banks in China - SHAO, Lin (2020)
This dissertation is an empirical investigation on the bank-specific and microeconomic determinants of default risk in Chinese commercial banks over 2014 to 2019 by adopting the dynamic panel data estimation techniques with two-step system GMM estimators. According to the reviewed literature on bank risk, there are four risk models in this study, and eight bank-specific determinants and two macroeconomic determinants are adopted as the independent variables in these models. As to the sources of the initial data in this study, the annual bank-specific data are accessible in the Bankscope database which provides comprehensive information on both list and unlisted commercial banks in China, and the macroeconomic data is taken from the World Bank database. The initial sample includes all 259 commercial banks located in China over the period from 2014-2019, and the final sample used to perform the empirical analysis consists of 228 commercial banks after dropping 31 commercial banks from the original sample due to missing values or extreme values. The findings of this empirical study show that these variables are all significantly related to bank risk-taking in China, validating most of the hypothesis put forward in the chapter two of this thesis. Based on these findings, several strategies could be adopted by banks and policy makers to improve the stability of Chinese banking sector, including raising bank liquidity, capitalization, efficiency, asset quality, and bank size, and lowering funding liquidity, profitability, and asset growth.